Chronic Poststernotomy Pain after Cardiac Surgery: Correlation of Computed Tomography Findings on Sternal Healing with Postoperative Chest Pain - Papadopoulos, Nestoras; Hacibaramoglu, Meltem; Kati, Canan; Muller, Dominik; Flöter, Julius; Moritz, Anton (The Thoracic and Cardiovascular Surgeon, 2013)
Background The aim of this study was to correlate CT findings on sternal healing to late postoperative chest pain after median sternotomy.Methods 71 patients with a mean age of 69 ± 8.4 years were examined by CT-scan for normal or imperfect sternal healing at a mean follow-up time of 1.4 ± 1.6 years. Patients completed a questionnaire for chest and shoulder pain using a multidimensional pain score and visual analog scale.Results Total 48 patients showed complete and 23 incomplete sternal healing. Although pain incidence was insignificantly higher after incomplete then after complete sternal healing (56.5% vs. 43%) pain intensity in the regions of chest and shoulder was almost equal between the two groups. Yet patients with a dehiscence over 3 mm in width had a significant higher chest pain intensity (17.5 ± 20 mm) compared with patients with a minor dehiscence (3.7 ± 8, mm p = 0.04) and those with normal sternal healing (8.1 ± 16 mm, p = 0.05). Furthermore, a dehiscence in more than one sternal segment led to a significantly higher pain intensity (chest: 18.8 ± 26 mm, shoulder: 23 ± 24 mm) compared with a dehiscence localized in only one segment (chest: 8.1 ± 18 mm, p = 0.04, shoulder: 4.6 ± 8.7 mm, p = 0.037).Conclusion In general, there is only a weak correlation between late postoperative chest pain and quality of sternal reunion. However, with an extent of failed sternal reunion over a width of 3 mm and the presence of imperfect ossification in more than one segment of the sternum, a significant increase of pain intensity in the regions of chest and shoulder was observed.
Keywords: chest wall; computed tomography; sternum